Communicational Structure Analysis of a Psychotherapy Transaction - Scheflen, M.D (Indiana University Press, 1973)
This book explains the new structural methods of research in behavior and communication. This application of the method grew out of discoveries made during an investigation of the psychotherapy of schizophrenia, when it was found that even trained observers could not agree on what they had actually seen during a given session. When the sessions were filmed, the observers' objectivity improved but the basic problem of data reduction and interpretation remained unsolved. The final solution came when the directors of research applied the method of context analysis worked out in the field of communication research. Dr. Scheflen shows that analysis of communicational structure, with emphasis on non-verbal behavior-"body language"-is a logical approach to studies of this type.